2003
DOI: 10.1126/science.1089134
|View full text |Cite
|
Sign up to set email alerts
|

Does Rejection Hurt? An fMRI Study of Social Exclusion

Abstract: A neuroimaging study examined the neural correlates of social exclusion and tested the hypothesis that the brain bases of social pain are similar to those of physical pain. Participants were scanned while playing a virtual ball-tossing game in which they were ultimately excluded. Paralleling results from physical pain studies, the anterior cingulate cortex (ACC) was more active during exclusion than during inclusion and correlated positively with self-reported distress. Right ventral prefrontal cortex (RVPFC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

108
2,023
20
56

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 3,083 publications
(2,268 citation statements)
references
References 21 publications
108
2,023
20
56
Order By: Relevance
“…Most importantly in terms of the pain of paying, however, we found that activation in the insula during the period when subjects first saw the price correlated negatively with purchasing decisions (figure 2c). Insula activation has previously been observed in connection with aversive stimuli such as disgusting odours (Wicker et al 2003), unfairness (Sanfey et al 2003) and social exclusion (Eisenberger et al 2003). These results support the idea that when the delayed costs of immediate indulgence are not explicitly represented (as in, e.g.…”
Section: Spending and Savingsupporting
confidence: 75%
“…Most importantly in terms of the pain of paying, however, we found that activation in the insula during the period when subjects first saw the price correlated negatively with purchasing decisions (figure 2c). Insula activation has previously been observed in connection with aversive stimuli such as disgusting odours (Wicker et al 2003), unfairness (Sanfey et al 2003) and social exclusion (Eisenberger et al 2003). These results support the idea that when the delayed costs of immediate indulgence are not explicitly represented (as in, e.g.…”
Section: Spending and Savingsupporting
confidence: 75%
“…Results showed that adolescents with a history of rejection, compared to their socially accepted counterparts, showed increased activation of the dACC and anterior prefrontal cortex (PFC) following such incidental experiences of exclusion. Activation in these regions have been linked to conflict monitoring, expectation violations, physical pain, and social inclusion (Botvinick, Cohen, & Carter, 2004;Eisenberger, Lieberman, & Williams, 2003;Shenhav, Botvinick, & Cohen, 2013;Somerville, Heatherton, & Kelley, 2006). Moreover, higher activation of the dACC and PFC have been linked to rejection sensitivity (Masten et al, 2009).…”
Section: Relationships With Peers and Executive Function Developmentmentioning
confidence: 99%
“…Pain includes sensory, affective and evaluative dimensions, whereas emotions can influence the affective dimension (Melzack and Casey, 1968). Recent studies showed a close connection of brain centers that involve pain and emotions (Eisenberger et al, 2003;Koyama et al, 2005;Vogt, 2005). Several authors (de Wied and Verbaten, 2001;Meagher et al, 2001;Rainville et al, 2005) agree that pleasant affective states reduce pain perception, whereas unpleasant affective states exacerbate it.…”
Section: Introductionmentioning
confidence: 99%